Evaluation of Load-Bearing Performance and Cost Efficiency in Steel-Welded and Modular Aluminum Rack Structures - Lenka Jakubovičová; Milan Vaško; František Synák (Machines)
The profile modular system offers variability, flexibility, ease of assembly, and corrosion resistance as well as non-time-consuming assembly while meeting the required conditions of the customer. It has a broad spectrum of usability. This article compares the results of a stress analysis solution for two variants of a rack structure, namely the original variant made by welding Jäkl profiles and the newly proposed design variant created with aluminum Bosch profiles. The finite element method (FEM) is used in computational analyses. FEM models are created using shell elements. Particular attention is given to the use of shell elements in the FEM and their suitability for finite element analyses of the selected structures. Finally, the advantages and disadvantages of both approaches are evaluated, including a safety assessment and an economic comparison of the variants.